Forgotten but not lost: Notes about the status of the often overlooked Chilean desert endemic Loasa rotundifolia (Loasaceae) - Rafael Acuña-Castillo; María Teresa Eyzaguirre; Ludovica Santilli; Nicolás Lavandero; Dylan Cohen (Gayana: Botanica)
Chile is a biodiversity hotspot for Loasaceae. Although relatively well known (especially compared to countries further north along the tropical Andes), it is expected that the number of taxa in Chile is bound to change due to taxonomic work on currently recognized taxa, new records for the country, and undescribed diversity. Loasa rotundifolia is endemic to the Atacama Desert and was described in 1893, however it has mostly been overlooked by recent national and regional Floristic catalogues that include Chile. It is a rare species known previously from only three herbarium collections worldwide. The main objective of this contribution is to provide a modern revision for this rare taxon, including an amended description, a description of its distributional range, ecological notes, and a preliminary assessment of its conservation status. We studied material in SGO and CONC, mapped the distribution of the species, and assessed its preliminary conservation status in GeoCAT. We found that Loasa rotundifolia is a distinct species due to its unique leaf morphology and habitat preferences. Our revision indicates that the species is phylogenetically part of Loasa ser. Macrospermae, endemic to Región de Atacama and we recommend it to be regarded as Endangered, according both to our GeoCAT analyses and the application of IUCN criteria.